IMPLEMENTASI THINGSPEAK SEBAGAI DATABASE PADA ALAT DETEKSI BANJIR MENGGUNAKAN ESP32 - Fauzan, Muhammad; Nurdin, Nurdin (CONTEN : Computer and Network Technology, 2024)
Abstract — Thingspeak is a website that is capable of storing readings from sensors sent by devices such as microcontrollers and is able to become a database for storing the results of the sensors sent. This tool is a series of simple tools that uses an ESP32 microcontroller and real-time monitoring media via smartphone. This flood detection tool using the HC-SR04 sensor consists of a tool frame made of iron, the HC-SR04 sensor and a panel box. The 12 V 5 Ah battery comes from a 50Wp solar panel and is the main source of power for this tool. The various electronic components in this tool include LCD, HC-SR04 sensor, relay and stampdown module. The HC-SR04 sensor plays a role in measuring water height in real time when placed on the river bank. When the sensor has detected a predetermined water level, it will send data to the microcontroller. The microcontroller will process the data and send it to a virtual application, which will display it virtually on the cellphone. Data will also be displayed on the LCD.